P049 Proteomic characterization of serum extracellular vesicles from newly diagnosed patients with inflammatory bowel disease. (30th January 2023) - Soleto, I; Baldan, M; Ramírez, C; Orejudo, M; García, S; Mercado, J; Azkargorta, M; Lloro, I; Ortega Moreno, L; Aldars Garcia, L; Riestra, S; Rivero, M; et al.
Abstract: Background: The etiology and pathogenesis of inflammatory bowel disease (IBD), Crohn's disease (CD), and ulcerative colitis (UC) are complex and the mechanisms that lead to the development of these diseases remain unclear. Extracellular vesicles (EVs) are small particles covered with a cell membrane, originating from the emitting cell, excreted into the extracellular medium, and subsequently captured by receptor cells. EVs have a role in multiple diseases and they could also have a function in IBD pathogenesis. Therefore, the analysis of EVs isolated from the serum of newly diagnosed IBD patients (before starting any treatment) may represent an appropriate experimental approach to elucidate their role in IBD pathogenesis. We aimed to evaluate EVs' composition and potential effects in the pathogenesis of IBD. Methods: The protein content of EVs isolated by size exclusion chromatography from the 500 µl of serum from 100 patients with IBD (50 patients with CD and 50 patients with UC) recently diagnosed and 50 healthy controls (HC) was characterized by proteomics and their size and concentration in serum by Nanoparticle tracking analysis (NTA). The biological function of EVs and alterations in signaling pathways related to IBD were determined using Ingenuity Pathways Analysis (IPA) to analyze the OMICs results. Results: A total of 1, 100 proteins have been identified, of which 105 proteins were differentially expressed by patients with CD versus HC, 111 proteins by patients with UC versus HC, and 32 proteins by patients with UC versus CD. IPA analysis revealed that proteins carried in EVs are involved in the dysregulation of immune pathways such as the acute phase response (Figure 1), LXR/RXR activation pathway (Figure 2), and the complement pathway. These pathways were regulated differentially in IBD patients compared with HC, but also when the CU group was compared with the CD group (Figure 3) being upregulated nuclear receptors signaling and cytotoxicity pathways. Conclusion: EVs carry proteins that can be involved in the dysregulation of the immune system in IBD; this effect would be different in UC and CD since their EVs show a differential profile. Consequently, EVs may play role in IBD pathogenesis and source of strong biomarkers candidates for diagnosis in UC and CD. Further studies on their specific function during IBD are warranted.